Routledge Handbook of Public Policy: A Review of the Book Edited by Araral et al., 2012 - Regassa, Tolcha Eshete; Debelo, Desalegn Beyene (Darul Yasin Al Sys, 2025)
Public policy has become an increasingly complex field of research and practice, requiring interdisciplinary perspectives and robust analytical frameworks. The Routledge Handbook of Public Policy, edited by Araral Jr. et al., offers a comprehensive overview of this complexity by reviewing public policy research and practice across 533 pages and 36 chapters organized into nine parts. Bringing together contributions from 58 authors, ranging from graduate students to seasoned professors, the volume explores the history, methods, analysis, and cyclical processes of public policy, including agenda-setting, formulation, decision-making, implementation, and evaluation. It also examines key analytical frameworks such as the advocacy coalition framework and the policy network model, alongside discussions of the influence of mass media and the role of policy design in policy transfer and diffusion. By synthesizing these diverse perspectives, the handbook serves as a valuable resource for understanding the intricacies of public policy formulation and evaluation, and it provides a substantive reference point for scholars and practitioners seeking to navigate contemporary policy debates and practices.